2020
DOI: 10.1021/acssuschemeng.0c02559
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Epoxy Synthesized from a Vanillin Derivative and Its Reinforcement Using Lignin-Containing Cellulose Nanofibrils

Abstract: A simple and rapid synthesis of biobased epoxy resin derived from vanillyl alcohol was performed, and its chemical structure was confirmed by FTIR and 1H and 13C NMR spectroscopies. Vanillin-based epoxy resin (VE) was further reinforced by lignin-containing cellulose nanofibrils (LCNFs) with different weight ratios. Characteristics of the resin and the nanocomposites, including the curing process, chemical structure, morphology, mechanical performance, thermo-mechanical properties, and thermal degradation beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 72 publications
3
41
0
Order By: Relevance
“…This result demonstrated that the DGEBDB is a potential bio-based monomer to improve the epoxy matrix’s fire resistance. Recently, bio-based vanillyl alcohol (VA)/lignin-containing cellulose nanofibrils (LCNFs) have been developed [ 171 ]. They have used the VA epoxy resins to improve the compatibility with LCNFs.…”
Section: Applications Of Vanillin-based Resinsmentioning
confidence: 99%
“…This result demonstrated that the DGEBDB is a potential bio-based monomer to improve the epoxy matrix’s fire resistance. Recently, bio-based vanillyl alcohol (VA)/lignin-containing cellulose nanofibrils (LCNFs) have been developed [ 171 ]. They have used the VA epoxy resins to improve the compatibility with LCNFs.…”
Section: Applications Of Vanillin-based Resinsmentioning
confidence: 99%
“…[5][6][7] One approach to build new functionality and improve performance is to fabricate biobased nanocomposites. [8][9][10][11] Nanoparticles have already been widely used to enhance the performance of the polymer matrix. Extensive research has been reported with petroleum based polymer matrices, though far fewer studies have been carried out with biobased polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, these composites are being considered for ballistic armors [ 27 , 28 , 29 , 30 ]. More recently, several researchers have been investigating the NLF waste as a source of nanocrystalline cellulose (NCC) [ 31 , 32 , 33 , 34 , 35 , 36 ], a strong nanomaterial, which can be used to produce several important products, such as nanocomposites, ion exchange membranes, films for electronics devices, and others [ 36 ].…”
Section: Introductionmentioning
confidence: 99%